In Vitro Study of Red Betel Leaves as Lymphocyte Cell Proliferator and Colorectal Cancer Cytotoxic Agent in Widr Cells - Pratama, Rahadian; Safithri, Mega; Umar, Mutmainnah Agustiawan; Tarman, Kustiariyah (Universitas Djuanda, 2024)
Colorectal cancer remains a leading cause of mortality worldwide and is closely linked to the immune system, particularly lymphocytes. This study evaluated the ethyl acetate fraction of red betel (Piper crocatum Ruiz & Pav) leaf ethanol extract for its anticancer activity against WiDr colon cancer cells and its effect on lymphocyte cell proliferation. Using MTT assays, the fraction showed significant WiDr cell inhibition (98.18% ± 1.21% at 500 ppm) and enhanced lymphocyte viability (143.3% ± 19.46% at 20 ppm). These results suggest the ethyl acetate fraction serves both as an effective anticancer agent against WiDr cells and as a promoter of lymphocyte proliferation, offering potential for dual therapeutic application.